Pengaruh CAR, NPL, BOPO Dan LDR terhadap Retrun on Assets pada Bank Pembangunan Daerah: - Moh Iklin (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to study and understand the effect of CAR, BOPO and NPL simultaneously on the Return On Assets of Regional Development Banks throughout Java Island for the period 2005 – 2021. And also to examine and understand the effect of CAR, NPL, BOPO and LDR partially on Return On Assets of Regional Development Banks throughout Java Island for the period 2005 – 2021. The population used in this study are Regional Development Banks throughout Java Island from 2005 to 2021 which have complete and published financial reports. The type of data used in this research is secondary data. Purposive Sampling Technique. Collecting data in this study using the documentation method. The analysis technique used is multiple linear regression with a significance level of 5%. The results showed that CAR partially had a significant positive effect on Profitability (ROA). BOPO partially has a significant positive effect on Profitability (ROA). NPL partially has a significant positive effect on Profitability (ROA). LDR partially has a significant positive effect on Profitability (ROA). CAR, NPL, BOPO and LDR jointly affect Profitability (ROA). Keywords: CAR, NPL, BOPO, LDR dan Return on Assets